EFEKTIFITAS MANAGEMENT STRES TERHADAP TINGKAT STRES IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN - Nurun Ayati Khasanah; Sri Wardini Puji Lestari; Dwi Nurhidayati (MEDICA MAJAPAHIT, 2025)
Childbirth is an event full of stress for most mothers giving birth, causing increased pain, fear, and anxiety, especially in first-time mothers. In Indonesia, research conducted on third-trimester primigravida found that 33.93% experienced stress. Objective: To determine the effect of stress management on the stress levels of third-trimester pregnant women in facing childbirth. This study uses an analytical observational method with a cross-sectional approach. The population consists of all third-trimester pregnant women, and the sample is 35, with analysis using the Wilcoxon statistical test. The hypothesis used is that there is a relationship if p < 0.05. Research results Most respondents (55.6%) experienced mild stress before being given stress management treatment. And all respondents (100.0%) did not experience stress or were normal after being given stress management treatment. Based on the Wilcoxon statistical test, the significance value (p sign = 0.000) indicates that p < 0.05, thus H1 is accepted, meaning there is an effect of Stress Management on Third Trimester Pregnant Mothers' Stress Levels at BPM Mrs. Veronika in Tulus Bear Village, Tumpang District, Malang Regency. As a midwife, we can take several actions related to the possibility of stress in pregnant women by using stress management to reduce the stress levels in pregnant women when facing childbirth